2017
DOI: 10.1128/iai.00471-17
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Bone Marrow Sca-1 + CD44 + Mesenchymal Stem Cells Kill Avirulent Mycobacteria but Not Mycobacterium tuberculosis through Modulation of Cathelicidin Expression via the p38 Mitogen-Activated Protein Kinase-Dependent Pathway

Abstract: Mycobacterium tuberculosis primarily infects lung macrophages. However, a recent study showed that M. tuberculosis also infects and persists in a dormant form inside bone marrow mesenchymal stem cells (BM-MSCs) even after successful antibiotic therapy. However, the mechanism(s) by which M. tuberculosis survives in BM-MSCs is still not known. Like macrophages, BM-MSCs do not contain a well-defined endocytic pathway, which is known to play a central role in the clearance of internalized mycobacteria. Here, we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…Mycobacterium tuberculosis infected the CD271 + bone marrow mesenchymal stem cells via scavenger receptors MARCO and SR-B1, and mesenchymal stem cells controlled intracellular MTB using autophagic mechanisms [72]. Mesenchymal stem cells killed avirulent mycobacteria but not MTB via modulation of cathelicidin expression [73]. Moreover, CD271 + bone marrow mesenchymal stem cells harboring MTB are localized in the hypoxic niche in both mice and humans, a critical microenvironmental factor that is known to induce dormancy [74].…”
Section: Other Intracellular Nichesmentioning
confidence: 99%
“…Mycobacterium tuberculosis infected the CD271 + bone marrow mesenchymal stem cells via scavenger receptors MARCO and SR-B1, and mesenchymal stem cells controlled intracellular MTB using autophagic mechanisms [72]. Mesenchymal stem cells killed avirulent mycobacteria but not MTB via modulation of cathelicidin expression [73]. Moreover, CD271 + bone marrow mesenchymal stem cells harboring MTB are localized in the hypoxic niche in both mice and humans, a critical microenvironmental factor that is known to induce dormancy [74].…”
Section: Other Intracellular Nichesmentioning
confidence: 99%
“…LL-37 is active against a wide range of Gram-positive and -negative bacteria (6). Previous findings, including ours, have shown that LL-37 is able to kill nonpathogenic and pathogenic mycobacteria under in vitro and in vivo conditions (7)(8)(9). The LL-37 peptide present in neutrophil extracellular traps is engulfed by macrophages to enhance intracellular killing of mycobacteria.…”
mentioning
confidence: 59%
“…Intracellular survival assay M. tuberculosis, MtbΔLprE, MtbΔLprE::LprE, Msm::pSMT3, Msm::LprE, MsmΔ5043, and MsmΔ5043::LprE strains were grown to mid-exponential phase. THP-1 monocytes were treated with PMA (20 nM) for 18 h and then infected at MOI 10 as described previously (7,22). Bacterial colonies were enumerated after 3 and 21 d for M. smegmatis and M. tuberculosis, respectively.…”
Section: Gfp Immunostainingmentioning
confidence: 99%
“…In vivo studies using allogenic murine MSCs have also implicated cathelicidin as a key AMP for bacterial killing (Johnson et al, 2017). Cathelicidin acts through TLR2/4-IRAK-4-dependent pathways in order to establish effective killing of mycobacteria (Naik et al, 2017). Interestingly, M. tuberculosis (Mtb) has developed a survival mechanism that disrupts this pathway and suppresses the antimicrobial effect of BM-MSCs via downregulation of CAMP gene expression (Naik et al, 2017).…”
Section: Direct Mechanisms Of Antimicrobial Effects Of Mscmentioning
confidence: 99%